(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
In the article, the activities of Inomjon Khidiraliev, the chairman of the Central Executive Committee of Turkestan and his participation in the education week organized in Tashkent in March 1923, and his thoughts on the solution of current problems in the education system, were analyzed with the help of periodicals and scientific literatures.